2021
DOI: 10.2196/28680
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant Women’s Attitudes Toward and Experiences With a Tablet Intervention to Promote Safety Behaviors in a Randomized Controlled Trial: Qualitative Study

Abstract: Background Intimate partner violence (IPV) is recognized as a global health problem. Women with low education and limited resources are more vulnerable, as are immigrant women. There is a lack of evidence on how health care professionals should communicate about and intervene against IPV during pregnancy. Earlier research has shown that when women manage digital questionnaires, they are more likely to disclose IPV. However, little is known about how women experience eHealth interventions with safet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Few women with Pakistani and Somali background participated in our study. Studies have showed that migrant women may be sceptic to participate in research due to cultural differences, language barriers and lack of trust regarding anonymity and confidentiality [30][31][32] . Migrants from Pakistan, Somalia and Central and Eastern Europe constitute the vast majority of childbearing women in Norway 23 .…”
Section: Research Papermentioning
confidence: 99%
“…Few women with Pakistani and Somali background participated in our study. Studies have showed that migrant women may be sceptic to participate in research due to cultural differences, language barriers and lack of trust regarding anonymity and confidentiality [30][31][32] . Migrants from Pakistan, Somalia and Central and Eastern Europe constitute the vast majority of childbearing women in Norway 23 .…”
Section: Research Papermentioning
confidence: 99%
“…Although we did not detect any effect at the three-month follow-up, our tablet-based instrument can still be used in antenatal care. In qualitative interviews with women and midwives participating in the Safe Pregnancy trial, both groups viewed it as a supplement to face-to-face communication [ 66 , 67 ]. Further, the women suggested making the tablet intervention available in other settings where women meet health care professionals [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…In qualitative interviews with women and midwives participating in the Safe Pregnancy trial, both groups viewed it as a supplement to face-to-face communication [ 66 , 67 ]. Further, the women suggested making the tablet intervention available in other settings where women meet health care professionals [ 66 ]. The midwives reported that the short intervention video made it easier to address IPV, and as a help in a time-limited setting with many tasks and demands [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, studies have shown that women may not disclose IPV during face-to-face antenatal consultations due to self-blame or presence of their violent partner [15,17]. One way to address this issue would be to offer a digital self-administered screening tool for pregnant women [17][18][19][20], and if screening positive, to subsequently offer an intervention [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Further, a recent study from Norway investigating the effect of a digital intervention for the prevention of IPV indicated that women found the antenatal care setting a safe place both to respond to the IPV questions and to watch a video with safety behaviors. Yet, the participating women recommended that the digital intervention should be supplemented with a supporting dialogue with a midwife [ 19 ]. Hence, a trusting relationship with a supportive health care provider may be of importance for the ongoing dialogue about IPV when delivering digital screening and interventions.…”
Section: Introductionmentioning
confidence: 99%